Gender differences in financial well-being, financial socialization and financial knowledge among college students - Falahati, Leila; Paim, Laily (Marsland Press, 2011)
This study aims to determine the gender differences in the financial well-being, financial socialization and financial knowledge among college students. The sample comprised 2,430 students in six public and five private universities across Malaysia, which were randomly selected for the study. A self-administered questionnaire was used as the data collection method. The perceived financial well-being was measured by asking students to rate their level of satisfaction on a scale of one (not satisfied at all) to ten (very satisfied) on six items including the amount of savings, financial situation, ability to purchase, savings for emergency expenses, skills to manage money, and ability to spend. The results revealed significant gender differences in financial well-being, financial socialization and financial knowledge. Female students perceived a higher level of financial well-being and a lower level of financial knowledge and later age financial socialization.